Answer:
[tex]y=-3x+14[/tex] or [tex]3x+y=14[/tex]
Step-by-step explanation:
we have
[tex]y+1=-3(x-5)[/tex] ----> equation of the line into point-slope form
step 1
Convert to slope intercept form
The equation of the line into slope intercept form is equal to
[tex]y=mx+b[/tex]
so
[tex]y+1=-3(x-5)[/tex]
[tex]y+1=-3x+15[/tex]
[tex]y=-3x+15-1[/tex]
[tex]y=-3x+14[/tex] ----> equation of the line into slope intercept form
step 2
Convert to standard form
The equation of the line into standard form is equal to
[tex]Ax+By=C[/tex]
so
we have
[tex]y=-3x+14[/tex]
Adds 3x both sides
[tex]3x+y=14[/tex] ----> equation of the line in standard form